HIV in postpartum women: Still a turbulent time. (January 2022) - Cooper, Rebecca; Collini, Paul; Greig, Julia
Abstract: Introduction: The postpartum period can be a difficult time for women living with HIV (WLWH), affecting engagement with care. We repeated our 2000–2011 audit of postpartum medication adherence and engagement with care for WLWH against BHIVA guidelines. Methods: We retrospectively reviewed clinical records of WLWH who delivered their baby between June 2013 and December 2019. We recorded antiretroviral (ARV) management before, during and for 12 months after pregnancy; CD4 count and viral load (VL) at booking, 36 weeks' gestation, delivery, 1 and 12 months postpartum. We categorised any psychological and social problems and recorded timing of mental health assessments and follow-up appointments. Results: There were 72 pregnancies involving 61 women, median age 35 years, 44 African. 70/72 (97%) continued with ARVs after delivery for whom VL data were available for 61 (85%). 49/61 (80.3%) had an undetectable VL (vs 64% in 2012). Of the 12 with a detectable VL, 5/12 (42%) had virological failure (>400 copies/ml). 32 (44%) missed at least one HIV clinic follow-up appointment (vs 27% in 2012), of whom 9/32 (28%) had a detectable VL. Social or psychological problems were noted in 47%, 10/12 (83%) with detectable VL and 20/32 (63%) that had missed an appointment. Discussion: The same psychological and social difficulties as 10 years ago are still impacting HIV care. We are currently conducting a qualitative research study to help determine what measures can be taken to lessen their impact on their HIV care, through interviews with postpartum WLWH.